2015
DOI: 10.3171/2014.11.jns14594
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life in patients with vestibular schwannoma: an international multicenter cross-sectional study comparing microsurgery, stereotactic radiosurgery, observation, and nontumor controls

Abstract: abbreviatioNs AAO-HNS = American Academy of Otolaryngology-Head and Neck Surgery; CPA = cerebellopontine angle; GBI = Glasgow Benefit Inventory; HRQOL = health-related quality of life; IQR = interquartile range; MCID = minimum clinically important difference; PANQOL = Penn Acoustic Neuroma Quality-of-Life; PROMIS-10 = 10-item Patient-Reported Outcomes Measurement Information System; SF-36 = 36-Item Short Form Health Survey; SRS = stereotactic radiosurgery; VS = vestibular schwannoma. submitted March 18, 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
178
1
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(205 citation statements)
references
References 34 publications
(44 reference statements)
14
178
1
7
Order By: Relevance
“…5 Using the same measure, Robinett et al reported a similar finding at 0-5 years of follow up; however, no statistically significant difference in pain was iden- (29) 19 (15) 56 (43) 17 (13) 116 (29) 93 (23) 155 (38) 39 (10) 1.0 (reference) 0.62 (0. tified between groups after 5 years. 34 Other studies have similarly demonstrated that differences in pain are greatest early after treatment; however, this disparity significantly declines within several years.…”
Section: Impact Of Treatment On Headachementioning
confidence: 54%
See 1 more Smart Citation
“…5 Using the same measure, Robinett et al reported a similar finding at 0-5 years of follow up; however, no statistically significant difference in pain was iden- (29) 19 (15) 56 (43) 17 (13) 116 (29) 93 (23) 155 (38) 39 (10) 1.0 (reference) 0.62 (0. tified between groups after 5 years. 34 Other studies have similarly demonstrated that differences in pain are greatest early after treatment; however, this disparity significantly declines within several years.…”
Section: Impact Of Treatment On Headachementioning
confidence: 54%
“…5 We found that the greatest reduction of HRQOL resulted from the disease itself, while long-term differences between treatment modalities were generally small. Only 3 of the 7 PANQOL domains demonstrated a statistically significant difference during global comparison: facial function, balance, and pain, with the latter exhibiting the largest difference between treatment arms.…”
mentioning
confidence: 86%
“…5 A recent long-term study confirmed the usefulness of the initial wait and see policy in the small VS and a better quality of life in the patients treated by SRS rather than microsurgery. 6 In this regard, it should be pointed out that radiation can affect neurologic function even after many years while surgery determines immediate neurological deficit. The length of follow-up in the various studies can therefore influence the incidence of neurologic impairment also on hearing function after radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent metanalysis reported a better hearing function (70.2% vs. 50.3%, p < 0.001) and a similar tumour control rate (96.2% vs. 98.7%, p = 0.122) comparing stereotactic radiation with microsurgery for treating small (<3 cm) VS. 2 Similar data come from recent reviews. 5,6 The very first reports on SRS for VS used quite high dose schedules, ranging from 10 up to 25 Gy delivered in single fraction. Local control with this approach was high (90-100%) but a significant number of adverse effects were observed, first of all hearing loss.…”
Section: Stereotactic Radio-surgery (Srs)mentioning
confidence: 99%
“…4 Hence, Carlson et al reported that hearing outcome in long term follow up was as poor as 23%. 34 10 years after stereotactic radiosurgery. They also confirmed initial hearing levels and tumor size as prognostic factors.…”
Section: Discussionmentioning
confidence: 99%